Predicting intensive care needs in community-acquired pneumonia: clinical utility of the SMART-COP score in Southern India - Amitesh Pahari; Nitin Bhat (npj Primary Care Respiratory Medicine, 2026)
Abstract Background Community-acquired pneumonia (CAP) presents a severe burden in developing regions, requiring precise triage. Traditional severity scores like CURB-65 often predict mortality rather than the immediate need for intensive care. The SMART-COP score proves to be a promising alternative for early triaging. Methods A prospective, longitudinal observational study was conducted among 123 adult CAP patients at a teaching hospital in Manipal, Karnataka, India. Clinical, laboratory, and radiological data were collected to calculate the SMART-COP score within 24 hours of admission. Primary evaluated outcomes included Intensive Respiratory or Vasopressor Support (IRVS) requirement, intensive care unit (ICU) length of stay, and in-hospital mortality. Results The cohort’s mean age was 61.33 ± 15.98 years. A significant majority (77.2%) needed ICU admission, with 58.5% requiring IRVS (56.9% intensive respiratory support, 24.4% inotropes). The in-hospital mortality rate was 14.6%, with mean admission SMART-COP score being 4.15 ± 2.61. SMART-COP significantly outperformed CURB-65 in predicting IRVS (AUROC 0.901 vs. 0.805; DeLong’s p = 0.007). Spearman’s correlation revealed a weak-to-moderate positive relationship between the admission score and ICU duration among admitted patients (rho = 0.315; p = 0.002). A count-based negative-binomial regression model demonstrated that every 1-point score increase was associated with a rate ratio of 1.34 for expected ICU days across the cohort. Multivariable regression confirmed that acute physiological instability independently drove the requirement for IRVS, superseding chronic comorbidities. Conclusion This single-centre validation study indicates that the SMART-COP score is a useful bedside triage instrument. Routine application at the primary care level may assist in early risk stratification and timely referral.